The chemistry of bisallenes - Henning Hopf (Beilstein Journal of Organic Chemistry, 2012)
This review describes the preparation, structural properties and the use of bisallenes in organic synthesis for the first time. All classes of compounds containing at least two allene moieties are considered, starting from simple conjugated bisallenes and ending with allenes in which the two cumulenic units are connected by complex polycyclic ring systems, heteroatoms and/or heteroatom-containing tethers. Preparatively the bisallenes are especially useful in isomerization and cycloaddition reactions of all kinds leading to the respective target molecules with high atom economy and often in high yield. Bisallenes are hence substrates for generating molecular complexity in a small number of steps (high step economy).